The outcomes of specific surgically correctable congenital gastro-intestinal malformations at a tertiary level neonatal intensive care unit in South Africa - Ilhaam Abrahams; Lizelle Van Wyk; Corne De Vos (EL-Med-Pub, 2023)
Background: The outcome of neonates with congenital surgically correctable gastro-intestinal (GIT) malformations is poorly described in low middle income countries. Methods: A 5-year retrospective descriptive analysis of neonates admitted to a tertiary level neonatal intensive care unit (NICU), with congenital, surgically correctable GIT malformations, was performed. The primary outcome was the 30-day postoperative mortality as well as survival to 1 year. Secondary outcomes included patient demographics, clinical presentation as well as the burden of disease in our study population. Results: Eighty-four neonates met study criteria. The mean gestational age was 35 weeks (SD 3.19) and birthweight 2518g (SD 789.3). The most common congenital malformations were intestinal atresia (39%) followed by omphaloceles (21%). Associated systemic malformations were common (39%). The majority of neonates (88%) underwent surgery at a median age of 2 days (IQR 1.5-5). Ventilation was required in 19% of neonates preoperatively and 65% postoperatively. Full feeds were achieved at a median age of 13 days (IQR 9-18) after surgery. The 30 day-postoperative survival rate was 97% with a survival to discharge or transfer of 86%. Data for one year survival was available for 80% of neonates with a one-year survival rate of 75%. Conclusion: The 30-day postoperative survival was high in neonates with congenital, surgically correctable GIT malformations. Outcomes and burden on the healthcare system was dependent on the type of lesion. With early diagnosis and referral to a tertiary centre, good outcomes can be achieved. Neonates with congenital GIT malformations should have long term follow up to monitor growth and neurodevelopment as well as to address the high mortality post discharge.